Ideología, política y bienestar público en España (2008-2014) - Antonio Robles Egea (Cahiers de Civilisation Espagnole Contemporaine)
Political ideologies still have great influential power. When financial crises occurs, such as the recent one, take place solutions to economic and social problems depend on the ideological orientation that is at the service of politics and its various practical manifestations. The case of Spain shows that neoliberal-conservative ideologies have politically imposed their principles by limiting government expenditure on education, health and social assistance, along with other measures consistent with the reduction of the welfare state. The consequences have been harmful for those most in need within the population and also for the stability of the democratic system.